The effects of households’ and firms’ borrowing constraints on economic growth - Pereira, Maria da Conceição Costa (2008)
This paper considers an endogenous growth model with asymmetric information between lenders and borrowers, that leads to credit-rationing a proportion of borrowers. However, in contrast to the existing literature, in this model, both firms and consumers face borrowing constraints. Nonetheless, the borrowing constraints facing a firm and those encountered by a consumer have opposing effects on growth. Relaxing borrowing constraints on firms is growth- promoting, as more funds become available for productive investment. In contrast, relaxing borrowing constraints facing consumers has a detrimental effect, as funds are diverted from productive investment to consumption. Such an adverse effect may offset the externality effect present in the production function that would otherwise ensure perpetual growth. Furthermore, it is shown that the interaction between households’ and firms’ borrowing constraints may give rise to endogenous cycles.